The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1097/00019442-199800610-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Serum Anticholinergic Activity With Delirium in Elderly Medical Patients

Abstract: To investigate the hypothesis that elevated serum anticholinergic activity is independently associated with delirium in ill elderly persons, the authors performed a cross-sectional study of 67 acutely ill older medical inpatients. The presence of delirium was evaluated with the Confusion Assessment Method, and the presence of many delirium symptoms was measured by the Delirium Symptom Interview. Demographic data and clinical characteristics that may be important for the development of delirium were also collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 0 publications
2
102
0
10
Order By: Relevance
“…Increasing acetylcholine levels by use of cholinesterase inhibitors such as physostigmine has been shown to reverse delirium associated with anticholinergic drugs 1719. Serum anticholinergic activity, which reflects anticholinergic influences of both endogenous and exogenous drugs and their metabolites, has been shown in some studies to be increased in patients with delirium and to decline with the resolution of delirium 2022. By contrast, other studies did not find a clear association between serum anticholinergic activity and delirium,23,24 but this might be because serum anticholinergic activity does not accurately reflect central cholinergic function.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Increasing acetylcholine levels by use of cholinesterase inhibitors such as physostigmine has been shown to reverse delirium associated with anticholinergic drugs 1719. Serum anticholinergic activity, which reflects anticholinergic influences of both endogenous and exogenous drugs and their metabolites, has been shown in some studies to be increased in patients with delirium and to decline with the resolution of delirium 2022. By contrast, other studies did not find a clear association between serum anticholinergic activity and delirium,23,24 but this might be because serum anticholinergic activity does not accurately reflect central cholinergic function.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Anticholinergic activity is also associated with the occurrence and severity of delirium. 1 2 A number of studies have shown that anticholinergic medication use is a common precipitating risk factor. 3 4 While delirium is a multifactorial process, it is estimated that medications alone may account for 12%-39% of all cases of delirium.…”
mentioning
confidence: 99%
“…A state of cholinergic deficiency is one of the leading hypothetical mechanisms for delirium23 and elevated anticholinergic activity correlates positively with delirium severity 47. Anticholinergic medications and prior dementia, in which cerebral cholinergic deficiency is prominent, both predict delirium 48.…”
Section: Methodsmentioning
confidence: 99%
“…Flacker et al 47 found SAA levels to be more than doubled in delirium, and increased levels of SAA were also associated with a higher burden of delirium symptoms. Further work by the same group found that SAA levels were significantly higher during acute illness than at 1-month follow-up, with a decline in SAA levels with the resolution of delirium 78.…”
Section: Methodsmentioning
confidence: 99%